Small cell lung cancer mimicking lymphoma in CT and 68Ga-DOTA-NOC PET/CT: A case report. Issue 25 (June 2018) - Lu, Liyan; Li, Fengfang; Zhang, Yamei; Wang, Peng; Yin, Xindao; Li, Wenbin
Abstract: Rationale: Small cell lung cancer accounts for 15-20% of all lung cancers and is the most common pulmonary neuroendocrine neoplasm. Most small cell lung cancers arise from lobar or main bronchi, the most common manifestations of small cell lung cancer is a large mass centrally located within the lung parenchyma or a mediastinal mass involving the hilus. Small cell lung cancer is easily ignored by clinicians without lung parenchyma and hilus involvement. Here, we report a case of small cell lung cancer, which was misdiagnosed as the lymphoma in contrast enhanced CT and 68 Ga-DOTA-NOC PET/CT imagings. Patient concerns: A 49-year-old male with chief complaint of discontinuous cough for 1 month. Diagnoses: Small cell lung cancer. Interventions: Radiotherapy and chemotherapy were given thereafter. Outcomes: The case had multiple enlarged lymph nodes due to tumor progression. Lessons: Small cell lung cancer is a malignant and progressive disease, and easy to be ignored in clinical. The case of small cell lung cancer without parenchyma and hilus involvement has never been reported before. Here, we report it and hope it provides a differential diagnosis for clinicians in the following similar cases.